2017
DOI: 10.5935/2359-4802.20170076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Central Blood Pressure and Arterial Stiffness in Practicing Long-Distance Walking Race

Abstract: Background: An ecological hiking occurs yearly in Brazil. It is a unique event because of its distance (310 km) and dynamics (mean of 62 km/day for 5 days with mean pace of 7.6 km/h). Although beneficial effects of moderate-intensity exercises are well-known, the effects of intense and long-duration exercise still require study. Objective:To evaluate the effects of mixed walking/running race on various blood pressure (BP) parameters 30 days before (A0), on the 2 nd (A2), 3 rd (A3), and 4 th (A4) days after com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
1
2
0
2
Order By: Relevance
“…Other publications that assessed marathoners presented results similar to ours, with no significant changes in arterial stiffness parameters during the exercise period [18,19]. A previous study on CEG also found no significant changes in PWV [20].…”
Section: Discussionsupporting
confidence: 86%
“…Other publications that assessed marathoners presented results similar to ours, with no significant changes in arterial stiffness parameters during the exercise period [18,19]. A previous study on CEG also found no significant changes in PWV [20].…”
Section: Discussionsupporting
confidence: 86%
“…A longitudinal study was conducted in July 2015 that evaluated 28 race walkers, including 24 men and 4 women, who participated in the “Ecological Walk of Goiás—2015” [7, 8]. The participants walked 310 km in 5 days (average 62 km/day), consisting of alternating periods of fast walking and running, at an average speed of 7.6 km/h.…”
Section: Methodsmentioning
confidence: 99%
“…Apesar de a tonometria arterial indireta ser considerada padrão-ouro na avaliação da rigidez arterial pela obtenção da VOPcf, a mensuração pelo método oscilométrico permite uma execução de forma mais simplificada, reprodutível e com resultados confiáveis. 214 , 215 , 220 , 221 …”
Section: Técnicas Disponíveis Para Verificação Dos Parâmetros Centrai...unclassified
“…Although indirect arterial tonometry is considered the gold standard for the evaluation of AS assessed by cfPWV, oscillometric measurement is a simpler method that provides more reproducible and reliable results. 214 , 215 , 220 , 221 …”
Section: Techniques Available For Checking Central and Arterial Stiff...mentioning
confidence: 99%